Genetic variability and individual assignment of Chinese indigenous sheep populations (Ovis aries) using microsatellites - Niu, L.L.; Li, H.B.; Ma, Y.H.; Du, L.X. (Wiley, 2012)
The purpose of this study was to assess the genetic characteristics of six breeds of Chinese local sheep using 19 microsatellite loci and to effectively validate statistical methods for individual assignment based on informative microsatellites. All the six breeds deviated from Hardy–Weinberg equilibrium expectations, while the majority of markers complied. The polymorphism information content (PIC) of overall loci for the six populations ranged from 0.283 (SRCRSP5) to 0.852 (OarVH72). Tibetan sheep were the most diverse population with the highest mean allelic richness (6.895), while Ujmuqin (UQ) harboured the lowest allelic richness (6.000). The F?statistics for the six populations were FIS?=??0.172, FIT?=??0.082 and FST?=?0.077, respectively. Furthermore, the pair?wise FIS revealed a moderate genetic differentiation among populations (P?<?0.01), indicating that all breeds can be considered genetically independent entities. The lowest genetic differentiation was between Tengchong (TC) and UQ (FST?=?0.041), and the highest one was between TC and Fat?tailed Han (FST?=?0.111). In comparing the three statistical models, we note that the seven microsatellite loci (MAF65, OarJMP58, SRCRSP9, MCM140, OarAE129, BM8125 and SRCRSP5) commonly used for individual assignment will ensure a powerful detection of individual origin, with accuracy up to 91.87%, when the likelihood?based method is used. Overall, these findings shed light onto the genetic characteristics of Chinese indigenous sheep and offer a set of microsatellite loci that is simple, economic and highly informative for individual assignment of Chinese sheep.